Determination of Stability Constants of Ibandronate Complexes with Ca(II), Mg(II) and Sr(II) - (:unkn) unknown (INT JOURNAL PHARMACEUTICAL RESEARCH & ALLIED SCIENCES, 2019)
In this study, a potentiometric titration method by Calvin-Bjerrum and Irwing-Rosotti was used to investigate binary complexes of ibandronate sodium, a nitrogen-containing bisphosphonate, with Ca(II), Mg(II) and Sr(II). Dissociation constants (pKa) of ibandronate sodium were measured and the stability constants of the complexes formed in aqueous solutions at 22 degrees C (I = 0.11 M NaClO4) were determined. The stoichiometry of ibandronate sodium/metal complexes was found as 1/1 for each metal ion.
Keywords: Ibandronate Metal Complexes; Bisphosphonates; pKa of Ibandronate; Potentiometric Titration; METAL-COMPLEXES; BISPHOSPHONATES; ACID; ALENDRONATE